Yield of corn genotypes fertilized with polymerized and conventional nitrogen: a uni and multivariate analysis (Research, Society and Development, 2020)
Corn is considered one of the main cereals grown worldwide, providing products widely used for human consumption. The application of nitrogen can influence its use by plants, due to the high dynamics that this element has in nature. In order to reduce nitrogen losses, urea coated with layers of polymers was developed, which allows the gradual release of nitrogen causing them to have less losses. In this way, the efficiency of nitrogen fertilization can be increased through the use of slow-release fertilizers. Therefore, this work aimed to evaluate the yield of corn genotypes fertilized with polymerized and conventional nitrogen, under a univariate and multivariate analysis. The study was conducted in the municipality of Mineiros, Goiás, Brazil. The experimental design used was a randomized block in a 4x2 factorial, totaling 8 treatments, corresponding to four corn cultivars (LG6030, MG600, 2B610 and CD3770) with two methods of nitrogen fertilization (polymerized urea 40% N and conventional 45% N) , in 4 repetitions. The variables were analyzed after harvest and the data submitted to univariate and multivariate analyzes. The analyzes were performed at the Rbio and Genes interface. The interaction between the factors was almost nil, and the source of genetic variation was largely responsible for the experimental divergence. At the end, it can be concluded that the univariate and multivariate analyzes were complementary, making it possible to recommend the cultivation of the genotype CD3770 for high corn yields using polymerized urea.